Statistical Convergence and Ideal Convergence of Sequences of Functions in 2-Normed Spaces - Saeed Sarabadan; Sorayya Talebi (International Journal of Mathematics and Mathematical Sciences)
We present various kinds of statistical convergence and ℐ-convergence for sequences of functions with values in 2-normed spaces and obtain a criterion for ℐ-convergence of sequences of functions in 2-normed spaces. We also define the notion of ℐ-equistatistically convergence and study ℐ-equi-statistically convergence of sequences of functions.